Zwrot polityczny w literaturze rosyjskiej, czyli „Lewy Front Sztuki” według Zachara Prilepina - Roman, Katarzyna Urszula (Wydawnictwo Nauka i Innowacje, 2014)
The paper concerns Russian contemporary politically engaged literature and takes into consideration the writings of an acclaimed Russian prose-writer, radical anti-Kremlin opposition activist – Zakhar Prilepin. A political turn in Russian contemporary literature is a way of raising an objection to the political authorities, who bring an incessant pressure on the society to reproduce the offi cial public discourse. It is also the act of uniting particularities of aesthetics, existence and politics, as well as breaking with the vision of literature distanced from the public issues. The common ground for Russian writers’ political commitment is a resistance to the postmodernism paradigm connected with an attempt to define the conditions and mechanisms of new ideology (in the „new realism” current). Deeply political writings of Prilepin seem to be an anti-liberal and anti-individualistic rebellion, as well as a thorough critical study of Russian contemporary society. The revolutionary prose-writer is against the doctrine of cultural pluralism, the activities of neo-liberal ruling elite, the growing political authority of Russian middle class and the dominant vision of collective memory.
A Political Turn in Russian Contemporary Literature or „Left Front of the Arts” by Zakhar Prilepin
Keywords: political turn; contemporary Russian literature; Zakhar Prilepin; politically engaged li terature; New realism current